2002
DOI: 10.1021/es010144t
|View full text |Cite
|
Sign up to set email alerts
|

Relative Dominance of Physical versus Chemical Effects on the Transport of Adhesion-Deficient Bacteria in Intact Cores from South Oyster, Virginia

Abstract: Bacterial transport experiments were conducted using intact sediment cores collected from sites on the Delmarva Peninsula near South Oyster, VA, to delineate the relative importance of physical and chemical heterogeneity in controlling transport of an adhesion-deficient bacterial strain. Electron microscopy revealed that the sediments consisted of quartz and feldspar with a variable amount of clay and iron and aluminum hydroxide coatings on the grains. A nonmotile, gram-negative indigenous groundwater strain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 28 publications
3
84
2
Order By: Relevance
“…However, exclusion factors (ratios of microbial velocity to solute velocity) as large as 1.6 were observed in laboratory core experiments using intact cores from the South Oyster site, and appear to be greatest in cores containing large amounts of finer-grained cross-bedded zones [31]. Why exclusion occurs more readily at laboratory scales than field scales in granular media remains a research question.…”
Section: Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exclusion factors (ratios of microbial velocity to solute velocity) as large as 1.6 were observed in laboratory core experiments using intact cores from the South Oyster site, and appear to be greatest in cores containing large amounts of finer-grained cross-bedded zones [31]. Why exclusion occurs more readily at laboratory scales than field scales in granular media remains a research question.…”
Section: Exclusionmentioning
confidence: 99%
“…Identification of the relative importance of physical and chemical heterogeneity is confounded by cross-correlation between the two; iron-rich minerals and coatings tend to be concentrated in finer-grained zones which also have lower permeability and higher collector efficiency. Dong et al [31] performed a laboratory study using cores from the South Oyster site, and concluded that variations in bacterial attachment could be explained by differences in collector efficiency (a physically based control) and that physical heterogeneity was dominant over chemical heterogeneity despite the existence of discrete bands of metal-rich grains. At the field scale, physical heterogeneity also appeared to be the dominant control on transport at the NC flow cell [59].…”
Section: Effects Of Iron Oxide Coatings/organic Maskingmentioning
confidence: 99%
“…Early breakthrough of colloids and biocolloids as compared to that of conservative tracers has been observed in several studies [Bales et al, 1989;Toran and Palumbo, 1992;Powelson et al, 1993;Grindrod et al, 1996;Dong et al, 2002;Keller et al, 2004;Vasiliadou and Chrysikopoulos, 2011;Sinton et al, 2012;Syngouna and Chrysikopoulos, 2013;Chrysikopoulos and Syngouna, 2014]. Colloid early breakthrough can be attributed to effective porosity reduction (colloids cannot penetrate smaller pores due to their inability to fit into them), preferential flow paths through high-conductivity regions, and exclusion from the lower-velocity regions [Chrysikopoulos and Abdel-Salam, 1997;Dong et al, 2002;Ginn, 2002;Ahfir et al, 2009], which can also be viewed as a reduction of the effective porosity of the porous medium [Morley et al, 1998]. The finite size of a colloid particle excludes it from the slowest moving portion of the parabolic velocity profile within a fracture or a pore throat, thus the effective particle velocity is increased, while the overall particle dispersion is reduced compared to Taylor dispersion, but with a tendency to increase with increasing particle size over a certain range of particle diameters Chrysikopoulos, 2000, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to quantify the influence of physical (size of the microbe and the porous medium, microbe concentration, water velocity, water content and surface roughness) and chemical (surface chemistry of the microbe and soil, and aqueous solution pH, ionic strength, and chemical composition) factors on microorganism transport in homogeneous porous media (Bradford et al, 2006;Chen and Walker, 2007;Dong et al, 2002;Hendry et al, 1999;Mccaulou et al, 1995;Mills et al, 1994;Yee et al, 2000). However, field experiments have frequently revealed that preferential pathways are a major contributor to the overall transport of microbes because they are typically strongly retained in the soil matrix (Abu-Ashour et al, 1994;Bales et al, 1989;Jiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%